Active Tectonics of the Nantinghe Fault in Southeastern Tibetan Plateau and its Implications for Continental Collision - Shi, Feng; He, Honglin; Liu, Yiduo; Wei, Zhanyu; Sun, Haoyue (Frontiers in Earth Science, 2022)
Quantifying the structure and kinematics of active faults is the key to understanding the India-Eurasia continental collision. While the boundary faults of blocks in the southeastern Tibetan Plateau region have been under scrutiny for decades, relatively less attention has been paid to the active faults within the blocks. Here, we use structural, sedimentary, and geomorphic characteristics to constrain the late Quaternary kinematics and slip rates of the Nantinghe fault, a major fault within the southeastern Tibetan Plateau region. The Nantinghe fault is an active, dominantly left-lateral strike-slip fault that can be traced continuously for 500 km. We analyze the late Quaternary slip rates at five sites along the fault trace. The latest Quaternary apparent throw rates are typically less than 1 mm/a. The rate of strike-slip displacement is estimated to be an order of magnitude higher, 4.0 ± 0.6 (2σ) mm/a. Trenching suggests that active fault behavior is dominated by strike-slip faulting and reveals five earthquake events with refined information of timing in last the 5000 years, suggesting an averaged recurrence interval of ~1000 a. These observations agree with GPS-derived estimates and show that late Quaternary slip rates on the Nantinghe fault are comparable to those on other major active strike-slip faults in the southeastern Tibetan Plateau. The newly-obtained slip rates on the Nantinghe fault, integrated with previous estimates on other faults in this region, provide direct evidence that favors the continuum models over the rigid block ones, on the deformation mechanism in the India-Asia continental collision.